2014
DOI: 10.1177/0165025414535121
|View full text |Cite
|
Sign up to set email alerts
|

Canadian portrait of changes in family structure and preschool children’s behavioral outcomes

Abstract: Whereas US-based data have contributed to our understanding of family composition changes over the last decades, data on Canadian families are limited, and previous studies have stressed the need for in depth, longitudinal investigations. This article begins to fill this gap in the literature by providing a current and detailed portrait of family composition changes from 1996 to 2008 (Study 1). Additionally, we performed an analysis of the role of specific child, parent and family characteristics, in interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Divorce or separation of the parental couple upsets both the structure and interpersonal dynamics of the family and can increase the risk of children developing externalizing behaviors (Eriksen, Hvidtfeldt & Lilleor, 2017; Gosselin, Romano, Bell et al ., 2014; Weaver & Schofield, 2015). Externalizing behaviors are characterized by manifestations such as physical aggression, defiance, temper tantrums, hyperactivity, and attention problems.…”
Section: Introductionmentioning
confidence: 99%
“…Divorce or separation of the parental couple upsets both the structure and interpersonal dynamics of the family and can increase the risk of children developing externalizing behaviors (Eriksen, Hvidtfeldt & Lilleor, 2017; Gosselin, Romano, Bell et al ., 2014; Weaver & Schofield, 2015). Externalizing behaviors are characterized by manifestations such as physical aggression, defiance, temper tantrums, hyperactivity, and attention problems.…”
Section: Introductionmentioning
confidence: 99%
“…In a Canadian study of urban minorities, household size was positively associated with physical aggression (Gosselin et al, 2014). Another study looking at children in foster care found that the presence of more children in the home was associated with increased externalizing behavior problems (Harden & Whittaker, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have related this with the large number of minors living together in residential care institutions (Faris, & Felmlee, 2011;Gosselin et al 2014). However, Font (2015 indicates that the children living in residential childcare report having faced many behavioral problems before they arrived at these institutions.…”
mentioning
confidence: 98%